A discovery of witches. [Series 1] [videorecording (DVD)] - Goode, Matthew, 1978-; Palmer, Teresa, 1986-; Bluemel, Edward; Harkness, Deborah E., 1965- (Acorn, 2019)
When Diana Bishop, historian and witch, calls up an ancient, bewitched manuscript from Oxford's Bodleian Library, she knows she must solve its mysteries. She is offered help by the enigmatic Matthew Clairmont, but he's a vampire, and witches should never trust vampires.